Pengaruh Discount Dan Store Atmosphere Terhadap Impulsive Buying Pada Ruby Supemarket Kecamatan Terara Lombok Timur - Muhammad Azrul Fahmi; Weni Retnowati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine the effect of discounts and store atmosphere on impulsive buying at Ruby Supermarket Terara, East Lombok. The type of research used is associative research with a quantitative approach. The population used is all consumers who have made impulsive purchases at Ruby Supermarket Terara, East Lombok. The number of samples used in this research was 72 people using non-probability sampling as a research sampling technique. The results of this research show that; (1) Discounts have a positive and significant effect on impulsive buying5, (2) Store atmosphere has a positive and significant effect on impulsive buying with a significance of 0.043, because tcount > ttable (2.058>1.944) with a significance value below 0.05. Based on the results of this research, it is recommended that Ruby Supermarket Terara pay more attention to promotional strategies in the form of discounts applied, both in terms of the size of the discount given and the type of products or goods that receive discounts. Apart from that, the store atmosphere at Ruby Terara is further developed by adding various Unique and attractive ornaments that can attract consumers to visit.